161k views
1 vote
Solve by using the quadratic formula: Simplify

Solve by using the quadratic formula: Simplify-example-1

2 Answers

1 vote

Answer:

x =
(48 - √(1984) )/(-8)

x =
(48 + √(1984) )/(-8)

Explanation:

-4
x^(2) - 48x - 20 = 0

Remember, the quadratic formula is:

x =
\frac{-b +- \sqrt{b^(2) -4ac } }{2a}

A quardatic equation in standard form is;

a
x^(2) + bx + c

Substitute in the values and solve;


(48 +- √((-48)^2 - 4 * (-4) * (-20)) )/(2*(-4))

Simplify;


(48 +-√(2304 -320) )/(-8)

x =
(48 +- √(1984) )/(-8)

x =
(48 - √(1984) )/(-8)

x =
(48 + √(1984) )/(-8)

User Joseph Earl
by
6.3k points
3 votes

Answer:

-6 - square root 31, -6 + square root 31

User Semihcan Doken
by
6.1k points